The party and political landscape of Austria after the 2024 National Council elections - Dmitry V. Shmelev; Egor E. Belyachkov (Научно-аналитический вестник Института Европы РАН)
On September 29, 2024, elections to the National Council were held in Austria. According to their results, the extreme right-wing Austrian Freedom Party won the election with more than 28% of the votes. The turnout at the end of the election was 77,7%. More than 14 parties were on the ballot, including parliamentary and non-parliamentary parties. Members of the governing coalition of parties – the Austrian People’s Party and the Green Alternative – were defeated, losing the majority of seats in the lower house of parliament. The authors analyze the electoral programs of the main parties, the significance of the federal election results for the future of the key Austrian parties, as well as the regional specifics of voting, which reflected the ongoing electoral processes, but also confirmed, in the authors’ opinion, the deepening fragmentation of the party-political landscape of the Alpine Republic for the period 2022–2024. The article concludes that the main reason for the victory of the ultra-right was the attraction of a significant number of young voters to their side, as well as the failure of the federal government’s policies that contribute to the deepening of the economic crisis in the country. The authors forecast the formation of a government coalition and the future of each of the Austrian parliamentary parties in the short term, including the land elections of 2024–2025.